Respon Pertumbuhan Dan Produksi Beberapa Jenis Selada (Lactuca sativa L) Terhadap Konsentrasi Larutan Nutrisi AB Mix Pada Hidroponik Sistem Wick - Hartanti, Aprilia; Adibah, Ummi; Sulistiyowati, Retrno (Universitas Panca Marga, 2023)
Crop cultivation using the hydroponic method is one of the urban farming trends in metropolitan areas and aims to fulfill food security. Lettuce is one of the horticultural crops which have high economic value. Quality and the yield of several lettuce varieties (Lactuca sativa L) could be raised through the appropriate concentration of AB mix nutrients. This research aimed to determine the concentration of AB mix nutrients on the growth and yield of lettuce. The research design used in this research was Randomized Block Design (R.B.D) with the first single factor consisting of 3 levels, red leaf lettuce, green leaf lettuce, and curly lettuce. The second single factor is the concentration of AB mix solution consisting of 4 (four) levels, such as non-nutrients, 4 ml/liter, 8 ml/liter, and 12 ml/liter. The results showed that lettuce varieties had an effect on the plant length, stem diameter, root length, wet crop residue, and dry crop residue. The concentration of AB mix solution also affected the plant length, number of leaves, root length, wet crop residue, and dry crop residue. The relationship between the combination of several types of lettuce and the concentration of AB mix solution provided differences in leaf width, wet crop residue, and dry crop residue. Keywords: Types of lettuce 1), AB mix nutrient 2), hydroponic 3)